Burwell Bassett family papers - Bassett, Burwell, 1764-1841.
Incoming letters, wills and other estate papers, Bassett family genealogical material, and ship manifests and bills of lading, including several of Hyndman, Lancaster & Company, tobacco brokers of London, England. Subjects include national political and fiscal matters. Correspondents include William Byrd of Westover, Francis Fauquier, Sir William Gooch, Benjamin Harrison, Benjamin Watkins Leigh, Thomas Nelson, and Robert Carter Nicholas.
Keywords: Byrd, William, -- 1674-1744 -- Correspondence; Fauquier, Francis, -- 1704?-1768 -- Correspondence; Gooch, William, -- Sir, -- 1681-1751 -- Correspondence; Harrison, Benjamin, -- approximately 1726-1791 -- Correspondence; Leigh, Benjamin Watkins, -- 1781-1849 -- Correspondence; Nelson, Thomas, -- 1738-1789 -- Correspondence; Nicholas, Robert Carter, -- 1728-1780 -- Correspondence; Bassett family; Hyndman, Lancaster & Company (London, England); Advertising -- Tobacco; Genealogy; Merchants -- Great Britain -- History -- 18th century; Merchants -- Virginia -- New Kent County; Merchants -- Virginia -- Williamsburg; London (England) -- Commerce -- 18th century; New Kent County (Va.) -- Commerce; Virginia -- Commerce; Williamsburg (Va.) -- Commerce; Legislators -- Virginia; Merchants; Plantation owners; Representatives, U.S. Congress -- Virginia